Comparative Study: Traditional Form Of The Game Sepak Rago The Communities Of Kopah And West Sumatra - Wulandari, Nova Reza (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
This research is motivated by the traditional game, namely Sepak Rago, which is a game that has existed for a long time and is found in several regions in Indonesia. such as Minangkabau and Riau, especially Kenegerian Kopah, Kuantan Singingi Regency. In Minangkabau this game is known as Sipak Rago, while in Kenegerian Kopah it is Sepak Rago Tinggi. From these two areas, there are several differentiating aspects of this game. This research was carried out with the aim of revealing comparisons of game forms. The research method used is descriptive-qualitative. The object of research is the traditional game Sepak Rago in the Minangkabau community and the Kenegerian Kopah community. The types of data used are primary and secondary data, data collection techniques namely observation and documentation, as well as data analysis techniques that combine and collect all the data obtained and then checked, filtered until the data becomes valid. The results of this research concluded that this form of traditional game in Minangkabau and Kenegerian Kopah has several differentiating aspects, namely technique, player members, properties and other supporting elements in the Sepak Rago game in the region. Even so, this traditional game is an asset that must be preserved and passed on to future generations. This aims to ensure that future generations do not easily abandon the traditions and culture of their region. The existence of aspects that differentiate traditional games can also be an important thing to show people's identity through culture and traditions through traditional games.